Brazilian energy-related climate (in)action and the challenge of deep decarbonization - Basso,Larissa (2019)
Abstract We present the challenge of deep decarbonization, the state of play of major economies regarding it, Brazilian outcomes compared to its peers and political struggles that help explain these outcomes. By identifying key actors, their interests and how they interact in domestic politics in issues that are key to deep decarbonization, we explain why Brazil, despite the potential to be ahead of its peers, has been moving backwards, and how Brazilian stances in the climate regime are influenced by it. The research is based on a qualitative analysis of extensive empirical data (primary and secondary sources).